Descontinuum e continuum gramatical: um estudo descritivo-analítico da Gramática Metódica da Língua Portuguesa de Napoleão Mendes de Almeida - Silva, Alexandre José da (2014)
This dissertation, divided in four chapters, and positioned in line with research of the History of Linguistic Ideas, describes and analyses the Gramática Metódica da Língua Portuguesa, work from one of the most important grammar scholars and philologists from our Country s idiom, the eminent Napoleão Mendes de Almeida. For the study developed in this work, it was unavoidable to search at Gramática Metódica, references to be able to confirm that the compendium of the famous author walks tenuously between the descontinuum and the continuum grammatical. So, as we lean over the referred work we notice that the dialogue with referential authors to Napoleão Mendes de Almeida, has shown to fundamental, using as example Jerônimo Soares Barbosa Grammatica Philosophica da Língua Portuguesa, Ernesto Carneiro Ribeiro - Elementos de Grammatica Portugueza and Eduardo Carlos Pereira Grammatica Expositiva: curso superior. In the first chapter,we discusabout thetheoretical frameworkthat justifiedthe work, the History of LinguisticIdeas, in order toexamine howa particularlinguistic knowledgeis interpretedand analyzedover time. In the second, we treat not onlythe context of productionof Gramática Metódica da Língua Portuguesa, but alsowe will present anoverview of theeducationalsituation in Brazil, starting from the second half of thenineteenth centuryand reaching intothe 40sof the twentieth century. In the third chapter, we study the horizon of retrospection of grammar of the author,in order to investigate their walk between descontinuumand continuumgrammatical. This retrospection indicated that the references cited by him said a lot about his grammatical thought. In the fourth, we present the description and analysis, when we track the work itself. We observed and had some evidences that the Gramática Metódica da Língua Portuguesa transitioned between descontinuumand continuumgrammatical, since the grammatical concepts of other authors were presented, analyzed, and used and extended when necessary. Finally, we say that this essay isnot intended to be conclusive. In contrast, aims at opening new studies on one of the most important grammar of our language, ie GRAMÁTICA METÓDICA DA LÍNGUA PORTUGUESA